Study on joint radar and communication system based on OFDM-MIMO - Pan, Ruoyan (Nanyang Technological University, 2021)
The past decade has seen the rapid development of joint radar and communication (JRC) systems in both the civil and military fields. Due to the wide use of digital signal processing and microwave technology in the field of wireless communication, we can find a feasible way to achieve both communication and radar detection functions in a single platform. Orthogonal frequency division multiplexing (OFDM) technology provides great advantages in terms of reducing inter-symbol interference (ISI) and carrying more information with a large number of subcarriers. Besides, in order to improve the radar resolution and target parameter identification ability, the research of multi-input multi-output (MIMO) radar has become a development trend. MIMO radar antenna belongs to the mode of multiple transmitters and multiple receivers, which can obtain the waveform diversity gain, thus improving the radar target identification ability and resolution. This study investigates the radar techniques in the joint radar and communication (JRC) system based on MIMO-OFDM by focusing on radar target parameter estimation methods. In particular, this dissertation studies two methods of multiplexing including time division multiplexing (TDM), frequency division multiplexing (FDM), and especially proposes a new method for Doppler ambiguity resolution in the TDM based MIMO-OFDM JRC system.